2007
DOI: 10.1111/j.1651-2227.2007.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

The CUPDAY Study: prebiotic‐probiotic milk product in 1–3‐year‐old children attending childcare centres

Abstract: A milk containing probiotics and prebiotics reduced the number of days children attending child care who had four or more stools by 20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…One prospective RCT that enrolled 496 children in day care centers found that children consuming a synbiotic blend of Bifidobacterium lactis (strain CNCM I-3446), oligofructose, and acacia gum experienced a 20% reduction in the number of days with diarrhea. 95 The potential role(s) of prebiotics without probiotics for prevention or attenuation of acute gastroenteritis remains unclear.…”
Section: Acute Gastroenteritismentioning
confidence: 99%
“…One prospective RCT that enrolled 496 children in day care centers found that children consuming a synbiotic blend of Bifidobacterium lactis (strain CNCM I-3446), oligofructose, and acacia gum experienced a 20% reduction in the number of days with diarrhea. 95 The potential role(s) of prebiotics without probiotics for prevention or attenuation of acute gastroenteritis remains unclear.…”
Section: Acute Gastroenteritismentioning
confidence: 99%
“…The data on efficacy for prevention of morbidity has been limited to small studies, mainly hospital based with short follow up or day care center based, with small sample size and short follow-ups [21][22]. Until date, only three randomized controlled trials have reported role of probiotics in prevention of community-acquired diarrhea [18], [20], [23]. Of these, two were in day care centers [18], [20] one of which was in developed country [20].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Prebiotics may promote an increase in beneficial gut bacteria such as bifidobacteria 13,14 and support respiratory and intestinal health. [15][16][17] Another nutrient with immunomodulatory properties is yeast b-glucan, a polysaccharide isolated from the cell wall of Saccharomyces cerevisiae. 18 Consumption of yeast b-glucan has been associated with fewer symptoms of acute respiratory infection (ARI) in healthy adults.…”
mentioning
confidence: 99%